Photography and representation of the private school during the Francoism in Madrid. Between advertising and story - Ramos Zamora, Sara; Rabazas Romero, Teresa; Colmenar Orzaes, Carmen (Historia y Memoria de la Educación, 2018)
The use of photographs as sources for the History of Education is one of the new topics of contemporary historiography that is assuming a greater role today. This paper will focus on the value of images as a historical source for the purpose of studying certain representative elements of some private schools Madrid during Franco’s regime. The research revolves around the most characteristic representations of these schools, highlighting the spaces, religiousness, education and activities as elements of identity and distinction: museums, school exhibitions, sports, associations and artistic activities. The main sources of documentation used come from the photographic archive in the collection of teacher-training reports preserved in the fund Anselmo Romero Marin in the Museum of History of Education «Manuel Bartolome Cossio» of the Complutense University.